Public reason and courts - Langvatn, Silje Aambø 1976-; Kumm, Mattias 1967-; Sadurski, Wojciech 1950- (Cambridge University Press, 2020)
"Ever since John Rawls brought the term "public reason" into academic circulation in the mid- 1990s, public reason has been discussed as a criterion of political and legal legitimacy. The idea of public reason is often formulated as the requirement that a polity's political and legal impositions must be publicly justifiable - or possible to justify with reasons and reasoning that is accessible and reasonably acceptable to all subjects of the imposition. Requiring laws to be public justifiable may seen as a means to ensure that all subjects are taken into account, and thus to prevent laws with morally unacceptable outcomes for some groups and individuals. But the criterion of public reason and public justifiability is also associated with the idea that not only the outcomes of laws and public acts counts towards their legitimacy, but also the form and content of their justifications: A law that prohibits a certain religious practice may be perfectly legitimate if it is shown that the practice is a real danger to public health or safety, whereas other types of justifications -such as racist reasons and animus towards a religion- is seen as weakening its legitimacy, or rendering the law illegitimate altogether."
"This book has been made possible with the generous contribution from PluriCourts-Centre for the Study of the Legitimate Roles of the Judiciary in the Global Order, at the University of Oslo, who financed the international workshop Courts and Public Reason in Global Public Law July 2016, and the WZB Berlin Social Science Center who provided the facilities and administrative assistance. Several of the chapters in this volume were presented in early versions at this workshop, while others have been commissioned later."--ECIP Acknowledgements
Keywords: Rawls, John -- 1921-2002; Öffentlichkeit; Gerichtsverhandlung; Staatstätigkeit; Vernunft; Political questions and judicial power; Judicial process; Public policy (Law); Rawls, John / 1921-2002 / Influence; Rawls, John / 1921-2002; Influence (Literary, artistic, etc.); Konferenzschrift -- 2016